Numerical Simulation of Cooling System for Solar Simulator. (August 2019) - He, C; Zhang, M; Zhou, Y; Li, G; Ding, W J; Gu, Z F; Zhang, Y; Li, A
Abstract: The cooling system for the solar simulator was introduced, which contained wind-cooling system, water-cooling system, and refrigeration system. Then the numerical simulation of the wind-cooling system was numerical simulated. The solar simulator with 13 xenon lamp was modeled, and the flow and the heat transfer in the solar hood was simulated by the FLUENT. The flow field in the solar hood was studied, especially the flow near the xenon lamp and the collector. The result showed that the velocity of the most area in the solar hood was slow, but the area near the xenon lamp, because the flow area suddenly decreases, the velocity of the gas increased significantly, which is conducive to the heat exchange between the xenon lamp and the gas. The temperature of the xenon lamp was lower than 328 K, and the velocity on the surface of the xenon lamp was higher than 17 m/s, which met the operating requirement of the xenon lamp, and the temperature of the collector was lower than 308 K, and meet the operating requirement of the collector.